2000
DOI: 10.1046/j.1464-5491.2000.00359.x
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies to glutamic acid decarboxylase in diabetic patients from a multi‐ethnic Australian community: the Fremantle Diabetes Study

Abstract: The relatively low GADA prevalence in Anglo-Celt patients with Type 1 diabetes is a feature of this community-based study and suggests that GADA levels do fall with time, given the older age of the sample and a relatively long period between diagnosis and sampling. Southern Europeans had an even lower GADA prevalence, regardless of diabetes type. Variations in GADA frequency in diabetic patients of differing European ethnicity has implications for clinical management and healthcare planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
180
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 119 publications
(189 citation statements)
references
References 38 publications
7
180
2
Order By: Relevance
“…Baseline assessment (1993)(1994)(1995)(1996) At baseline a comprehensive history of diabetes and comorbid conditions was taken, a physical examination was performed and the patients provided fasting blood and urine samples for standard biochemical tests, including serum glucose, HbA 1c , serum lipoproteins and albumin : creatinine ratio (ACR) [20][21][22][23]. Complications were identified using standard definitions.…”
Section: Clinical and Laboratory Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Baseline assessment (1993)(1994)(1995)(1996) At baseline a comprehensive history of diabetes and comorbid conditions was taken, a physical examination was performed and the patients provided fasting blood and urine samples for standard biochemical tests, including serum glucose, HbA 1c , serum lipoproteins and albumin : creatinine ratio (ACR) [20][21][22][23]. Complications were identified using standard definitions.…”
Section: Clinical and Laboratory Methodsmentioning
confidence: 99%
“…Of 2258 diabetic patients identified between 1993 and 1996, 1426 (63%) were recruited to the FDS and 1294 (91%) had type 2 diabetes. Identification and recruitment methods, sample characteristics, including classification of diabetes and details of non-recruited patients, have been described elsewhere [20,21]. 31 December 2002, were invited to participate in a study of cognitive function.…”
Section: Subjectsmentioning
confidence: 99%
“…The Fremantle Diabetes Study (FDS) recruited 1,426 diabetic patients (63%) from 2,258 identified in a postcode-defined urban Australian community between 1993 and 1996. Details of the FDS, including patient characteristics and methods used to diagnose diabetes, have been described previously [14]. In February 2001, there were 587 FDS survivors aged ≥70 years, of whom 302 (51.4%) agreed to undergo cognitive assessment.…”
Section: Patientsmentioning
confidence: 99%
“…Detailed sociodemographic, clinical and biochemical data were available at FDS entry for the present 302 patients and these data were updated on recruitment to the present study [14]. In addition, the FDS database was linked to the Western Australia Data Linkage System (WADLS) [16].…”
Section: Baseline Assessmentmentioning
confidence: 99%
See 1 more Smart Citation